Y Emma Bovary aprendió a hablar en gallego... - Cecilia Fernández Santomé (Flaubert: Revue Critique et Génétique)
Flaubert’s works have been translated into an important number of languages all around the world. These versions present different solutions to the “problems” of Flaubert’s style. In fact, translated books content many aesthetic and formal modifications that are intimately related to the strategies actives into the literary system that receives the resultant text. However, there is a kind of double gaze in the translator’s work that hides the simultaneous development of other aspects that are not literary features. The Galician translation of Madame Bovary shows how stylistic choices are determined by extra-literary politics into a cultural system that is already not completely consolidated.